2015
DOI: 10.1021/acs.jpca.5b07202
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Lateral Substituents Influence the Excitation Energies of Hexaaza Lanthanide Macrocyclic Complexes: A Wave Function Theory and Density Functional Study

Abstract: The high interest in lanthanide chemistry, and particularly in their luminescence, has been encouraged by the need of understanding the lanthanide chemical coordination and how the design of new luminescent materials can be affected by this. This work is focused on the understanding of the electronic structure, bonding nature, and optical properties of a set of lanthanide hexaaza macrocyclic complexes, which can lead to potential optical applications. Here we found that the DFT ground state of the open-shell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…Nomenclature of the V[Ru,N( 1 ‐ 3 ; 5 )] and V(Ru,Cl) monosynaptic basins follows the nomenclature reported elsewhere, in which the electron basins are localized between Ru and N or Cl, but significantly closer to the nonmetal atoms. This could indicate that Ru‐N or Ru‐Cl are dative bonds, highly polarized toward N or Cl . The Ru core is structured according to the observations of QTAIM Laplacian maps (Figure ) and valence shell electron pair repulsion (VSEPR) rules .…”
Section: Resultsmentioning
confidence: 96%
“…Nomenclature of the V[Ru,N( 1 ‐ 3 ; 5 )] and V(Ru,Cl) monosynaptic basins follows the nomenclature reported elsewhere, in which the electron basins are localized between Ru and N or Cl, but significantly closer to the nonmetal atoms. This could indicate that Ru‐N or Ru‐Cl are dative bonds, highly polarized toward N or Cl . The Ru core is structured according to the observations of QTAIM Laplacian maps (Figure ) and valence shell electron pair repulsion (VSEPR) rules .…”
Section: Resultsmentioning
confidence: 96%
“…19,26 If the energies of the orbitals centered on the ligand and metal are similar, then charge-transfer bands are observed, and the direction of this electron transfer is determined by the relative energy levels of these orbitals. 27,28 Thus, metal-to-ligand charge transfer (MLCT) happens through the electron transfer from molecular orbitals with a metal character to those with a ligand character. 29,30 Also, ligand-to-metal charge transfer (LMCT) happens for the opposite direction, which is very common in metals with orbitals available for accepting electrons from the ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These mechanisms compete with other radiative and nonradiative deactivation processes happening from the excited states of systems, namely, photoinduced electron transfer (PET), , that are answerable for the quenching of luminescence in many cases. Also, if the electron transfer involves intramolecular rotation, then it can result in a state called twisted intramolecular charge transfer (TICT). , If the energies of the orbitals centered on the ligand and metal are similar, then charge-transfer bands are observed, and the direction of this electron transfer is determined by the relative energy levels of these orbitals. , Thus, metal-to-ligand charge transfer (MLCT) happens through the electron transfer from molecular orbitals with a metal character to those with a ligand character. , Also, ligand-to-metal charge transfer (LMCT) happens for the opposite direction, which is very common in metals with orbitals available for accepting electrons from the ligands. On the other hand, when the same molecule contains both donor and proton receptor groups in proximity, the proton can be transferred directly from the acid to the basic site in the excited state. This process is so-called intramolecular protons from excited state (ESIPT). , …”
Section: Introductionmentioning
confidence: 99%
“…In this concern, Rabanal‐Leon and Paez‐Hernandez, showed the variation of the electronic structure of hexaaza‐lanthanide macrocyclic complexes, and their modification via substitution of organic ligands, resulting in the tuning of their excitation energies by using wave function and density functional theory . It was shown that the open‐shell DFT ground state results from the manifold of low lying f states, having small HOMO−LUMO energy gaps.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[145][146][147] In this concern, Rabanal-Leon and Paez-Hernandez, showed the variation of the electronic structure of hexaaza-lanthanide macrocyclic complexes, and their modification via substitution of organic ligands, resulting in the tuning of their excitation energies by using wave function and density functional theory. [148] It [149][150][151] For the bis(dicyclooctatetraenyl)diuranium complex studied in two symmetries (D 2h and C 2 ), the optical and magnetic properties have been accounted for by Paez-Hernandez, showing that for both symmetries the preferred ground state of the complex is a quintuplet spin state denoting significant ferromagnetic coupling between the metal centers. [152] A benchmark study from ab initio calculations by Celis-Barros et al, [153] used a multi-configurational CASSCF and NEVPT2 procedures to include static and dynamical correlation effects and then spin-orbit coupling applied to berkelium (Bk), californium (Cf ), einsteinium (Es) and fermium (Fm) hexahalides.…”
Section: Lanthanide and Actinide Complexesmentioning
confidence: 99%